Genetic Signatures of Dairy Lactobacillus casei Group - Fontana, Alessandra; Zacconi, Carla; Morelli, Lorenzo (Frontiers in Microbiology, 2018)
Lactobacillus casei/Lactobacillus paracasei group of species contains strains adapted to a wide range of environments, from dairy products to intestinal tract of animals and fermented vegetables. Understanding the gene acquisitions and losses that induced such different adaptations, implies a comparison between complete genomes, since evolutionary differences spread on the whole sequence. This study compared 12 complete genomes of L. casei/paracasei dairy-niche isolates and 7 genomes of L. casei/paracasei isolated from other habitats (i.e., corn silage, human intestine, sauerkraut, beef, congee). Phylogenetic tree construction and average nucleotide identity (ANI) metric showed a clustering of the two dairy L. casei strains ATCC393 and LC5, indicating a lower genetic relatedness in comparison to the other strains. Genomic analysis revealed a core of 313 genes shared by dairy and non-dairy Lactic Acid bacteria (LAB), within a pan-genome of 9,462 genes. Functional category analyses highlighted the evolutionary genes decay of dairy isolates, particularly considering carbohydrates and amino acids metabolisms. Specifically, dairy L. casei/paracasei strains lost the ability to metabolize myo-inositol and taurine (i.e., iol and tau gene clusters). However, gene acquisitions by dairy strains were also highlighted, mostly related to defense mechanisms and host-pathogen interactions (i.e., yueB, esaA, and sle1). This study aimed to be a preliminary investigation on dairy and non-dairy marker genes that could be further characterized for probiotics or food applications.